RESTORING THE AESTHETIC FUNCTION IN ORAL REHABILITATION - Bogdan Bulancea; Lupu Costin; Catalina Holban Cioloca; Dana Gabriela Budala; Roxana Ionela Vasluianu; Cosmin Cretu; Dragos Nicolae Fratila; Cosmin Bida; Raluca Elena Baciu (Romanian Dental Association for Education, 2024)
The knowledge of the oral rehabilitation principles allows the complex approach of the patient, giving optimal aesthetic, biomechanical and biological results. The patient plays an important role in terms of taking responsibility for the aesthetic aspect. Restoring the aesthetic function involves knowledge of the facial parameters, the principles of restoring facial harmony as well as the geometric proportion of the artificial teeth. The aim of this study is to underlying the importance of the patient's evaluation, which has like a substract the conception of the esthetic rehabilitation, the patient's perception and the clinician evaluation, to ensure the succeful in prosthodontic treatment.The notion of aesthetic or unaesthetic can be interpreted differently, depending on the degree of culture and perception of the notion of "beauty and symmetry".